CIGB-300, an anti-CK2 peptide, inhibits angiogenesis, tumor cell invasion and metastasis in lung cancer models. (May 2017) - Benavent Acero, Fernando; Capobianco, Carla S.; Garona, Juan; Cirigliano, Stéfano M.; Perera, Yasser; Urtreger, Alejandro J.; Perea, Silvio E.; Alonso, Daniel F.; Farina, Hernan G.
Highlights: We examined the effect of CIGB-300, an anti-CK2 peptide, in lung tumor development. In vitro, CIGB-300 inhibited lung tumor cell adhesion, migration and invasion. CIGB-300 elicited an anti-angiogenic response in vivo . CIGB-300 systemic administration reduced lung tumor cell dissemination and colonization. Abstract: Objectives: Casein kinase 2 (CK2) is overexpressed in several types of cancer. It has more than 300 substrates mainly involved in DNA reparation and replication, chromatin remodeling and cellular growth. In recent years CK2 became an interesting target for anticancer drug development. CIGB-300 is a peptidic inhibitor of CK2 activity, designed to bind to the phospho-acceptor domain of CK2 substrates, impairing the correct phosphorylation by the enzyme. The aim of this work was to explore the antitumor effects of this inhibitor in preclinical lung cancer models. Materials and methods: Human H125 and murine 3LL Lewis lung carcinoma cell lines were used to evaluate the effect of CIGB-300 treatment in vitro . For this purpose, adhesion, migration and invasion capabilities of cancer cells were tested. Proteolytic activity of tumor cell-secreted uPA and MMP after CIGB-300 incubation was also analyzed. In vivo anticancer efficacy of the peptide was evaluated using experimental and spontaneous lung colonization assays in C57BL/6 mice. Finally, in order to test the effect of CIGB-300 on tumor cell-induced angiogenesis, a modified Matrigel plug assay was conducted. Results and conclusion: We demonstrate that treatment with low micromolar concentrations of CIGB-300 caused a drastic reduction of adhesion, migration and invasion of lung cancer cells. Reduced invasiveness after CIGB-300 incubation was associated with decreased proteolytic activity of tumor cell-conditioned medium. In vivo, intravenous administration of CIGB-300 (10 mg/kg) markly decreased lung colonization and metastasis development of 3LL cells. Interestingly, after 5 days of systemic treatment with CIGB-300, tumor cell-driven neovascularization was significantly reduced in comparison to control group. Altogether our data suggest an important role of CK2 in lung tumor development, suggesting a potential use of CIGB-300 as a novel therapeutic agent against lung cancer.